Treatment strategies impacting ceftiofur resistance among enteric bacteria in cattle - Kanwar, Neena (Kansas State University, 2014)
A randomized controlled field trial was designed to evaluate the effects of two treatment strategies on ceftiofur and tetracycline resistances in feedlot cattle. The two strategies consisted of administering ceftiofur crystalline-free acid administration (CCFA) at either one or else all of the steers within a pen, and subsequent feeding/not feeding of therapeutic doses of chlortetracycline. Both strategies were hypothesized to reduce ceftiofur resistance. The effects of treatment strategies were evaluated via metagenome-based and culture-based assays. In this 26-day study, 176 steers were allocated to 16 pens of 11 steers each. The two strategies were randomly assigned to the pens in a two-way full-factorial manner resulting in four treatment groups. The blaCMY-2, blaCTX-M, tet(A), tet(B), and 16S rRNA gene copies/g feces were quantified using qRT-PCR from fecal community DNA. Antimicrobial susceptibility profiles were determined using microbroth dilution technique from the non-type-specific (NTS) E. coli isolates (n=1,050). The NTS E. coli DNA was screened for the presence of blaCMY-2, tet(A), and tet(B) genes. Pens in which all the steers received CCFA treatment showed an increase in blaCMY-2 and blaCTX-M log10 gene copies/g feces and in the proportion of ceftiofur-resistant and blaCMY-2 positive NTS E. coli. This was in contrast to the pens where only one animal received CCFA treatment. There was a significant decrease in quantities of tetracycline genes in community DNA in pens where all animals received CCFA treatment. In contrast to metagenome-based assay results, culture-based assays indicated an increase in the proportion of tetracycline resistant NTS E. coli upon CCFA treatment. Thereafter, chlortetracycline administration led to rapid expansion both of ceftiofur (blaCMY-2, blaCTX-M) and tetracycline [tet(A) and tet(B)] log10 gene copies/g feces. Chlortetracycline treatment delayed the return of the ceftiofur resistance prevalence to baseline among NTS E. coli and thus did not lead to the hypothesized decrease in ceftiofur resistance. Our data suggest that chlortetracycline use is contraindicated when attempting to avoid expansion of resistance to critically important 3rd generation cephalosporins in feedlot cattle. Further studies are required to better establish the animal-level effects of co-housing antimicrobial-treated and non-treated animals together at varying ratios on the levels of antimicrobial resistance.
Keywords: Antimicrobial resistance; Ceftiofur; Susceptibility profiles; Critically important antimicrobials; Resistance genes; Tetracycline; Epidemiology (0766); Microbiology (0410); Molecular Biology (0307)